2013
DOI: 10.1167/iovs.12-10127
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Rescue of Oxygen-Induced Retinopathy in Mice by Norrin

Abstract: Modulation of Wnt-signaling improves retinal vascularization and accelerates vascular recovery after induction of retinopathy in the OIR mouse. Activation of Wnt-signaling (norrin) and inhibition of Wnt-canonical signaling (DKK1) result in similar improvement, indicating that norrin promotes improved vascularization, at least in part, by way of noncanonical Wnt-signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…DKK1 treatment is known to decrease retinal tuft formation in a rat OIR model by inhibiting Wnt canonical signaling [30]. In our OIR model, DKK1 Tg mice displayed decreased retinal vessel density (84 % of wild-type levels) and increased avascular area (187 % of wild-type), in agreement with earlier observations in rats (Fig.…”
Section: Resultssupporting
confidence: 92%
“…DKK1 treatment is known to decrease retinal tuft formation in a rat OIR model by inhibiting Wnt canonical signaling [30]. In our OIR model, DKK1 Tg mice displayed decreased retinal vessel density (84 % of wild-type levels) and increased avascular area (187 % of wild-type), in agreement with earlier observations in rats (Fig.…”
Section: Resultssupporting
confidence: 92%
“…This disorganization is likely the result of a substantial percentage of retinal astrocytes and the fact that surviving astrocytes are impaired in their capacity to guide capillary growth (Bucher et al, 2013). In this environment, treatment with Norrin somewhat tames neovascular response and ultimately accelerates the revascularization of the central retina (Tokunaga et al, 2013). Other treatments have been reported that reduce the severity of aggressive neovascular growth in this model and facilitate re-establishment of normal vascular beds in ablated zones (May, 2012)…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen-induced retinopathy (OIR) model using C57BL/6J or Thy1 -YFP transgenic mice neonates was used as previously described (Smith et al, 1994; Tokunaga et al, 2014, 2013). This model is well characterized and widely used for experimental studies of retinal ischemia (Smith et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, the PBS-treated eyes had a significant decrease (20%) in the avascular area compared with the noninjected fellow eyes (P ¼ 0.016), an effect seen previously as well. 18,19 Retinal recovery can occur in response to injury such as that caused by an intravitreal injection. It is feasible that low-grade inflammation following ocular penetration may have a role in retinal recovery.…”
Section: Avascular Areamentioning
confidence: 99%